1994
DOI: 10.2527/1994.72102735x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary canola on fatty acid composition of bovine adipose tissue, muscle, kidney, and liver1

Abstract: The purpose of this study was to determine effects of feeding canola and soybean products as protein supplements on fatty acid composition of adipose tissue and muscle of slaughter bulls and steers and on fatty acid composition of kidney and liver total lipids of bulls. Products included canola meal (CM), extruded canola (EC, full-fat), ground canola (GC, full-fat), soybean meal (SBM), and extruded soybeans (ES, full-fat). Tissues were obtained at slaughter from 75 crossbred beef bulls and 50 crossbred beef st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
2
10

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 27 publications
7
42
2
10
Order By: Relevance
“…Strzetelski et al (1992) found that feeding fattening bulls ad libitum with complete mixtures containing 15 or 30% rape seed did not decrease dry matter intake compared with the control group. Similar results were obtained by other authors feeding fattening bulls different rations containing different sources and levels of vegetable or fish oils (Rule et al, 1994;Kreuzer et al, 1995;Scollan et al, 1997b;Strzetelski et al, 1998a;Choi et al, 1999). In other experiments, feeding diets containing linseed, sunflower or soyabean seed decreased dry matter intake (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…Strzetelski et al (1992) found that feeding fattening bulls ad libitum with complete mixtures containing 15 or 30% rape seed did not decrease dry matter intake compared with the control group. Similar results were obtained by other authors feeding fattening bulls different rations containing different sources and levels of vegetable or fish oils (Rule et al, 1994;Kreuzer et al, 1995;Scollan et al, 1997b;Strzetelski et al, 1998a;Choi et al, 1999). In other experiments, feeding diets containing linseed, sunflower or soyabean seed decreased dry matter intake (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…High levels of C18:1t11 have previously been reported as a result of inclusion of vegetable oils in the diet. O' Kelly and Speirs (1993) found that feeding safflower oil could dramatically increase the amount of Rule et al 1994;Mandell et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Mills et al (1992) found fatty acid composition of Holstein and beef steers was unaffected by forage type (corn silage versus haylage) but longissimus muscle from steers fed fishmeal had higher palmitoleic and lower stearic acid contents than meat from animals fed soybean meal. Rule et al (1994) observed that feeding full-fat canola can alter fatty acid composition of bovine muscle, fat, kidney and liver by increasing levels of C18:0 and C18:1 and decreasing C16:0.…”
mentioning
confidence: 98%
“…It has been well documented that high-energy grain diets produce a more acceptable or more intense flavor in red meats than low energy diets. In addition, diet can influence fatty acid composition of bovine tissues (Mills et al 1992;Rule et al 1994). Offer and Offer (1994) indicated distillery byproducts such as malt distillers' or dark grains (from Scotch Whiskey production) when fed to ruminants, may potentially reduce the degree of saturation of both tissue and milk fat, producing potentially "healthier" meat and milk.…”
mentioning
confidence: 99%